Combination of White Blood Cell Count and Left Shift Level Real‐Timely Reflects a Course of Bacterial Infection. Issue 5 (13th September 2013) - Ishimine, Nau; Honda, Takayuki; Yoshizawa, Akihiko; Kawasaki, Kenji; Sugano, Mitsutoshi; Kobayashi, Yukihiro; Matsumoto, Takehisa
<x xml:space="preserve">Abstract</x> Background The efficacy of white blood cell (WBC) count and left shift in predicting bacterial infections has been controversial. The aim of this study was to prove that WBC count and left shift reflect a course of bacterial infection. Materials Six patients in whom the onset of bacterial infection had been determined and successful treatment had been done were selected. Manual 100‐cell differential counts were repeated at least every 24 hr. Results WBC count and left shift divided a course of bacterial infection into five phases. In the first phase of bacterial infection (0–10 hr after the onset), WBC count decreased to fewer than reference range without left shift. In the second phase (about 10–20 hr), low WBC count continued and left shift appeared. In the third phase (one to some days), WBC count increased above reference range with left shift. In the fourth phase (some to several days), high WBC count continued without left shift. In the fifth phase, WBC count went down into reference range without left shift. Conclusions A combination of WBC count and left shift real‐timely reflected a course of bacterial infection from the onset to healing. And we could judge which bacterial infection is adequately treated or not only by the above two routine laboratory tests.